The influence of the community climate on users' knowledge-sharing intention: the social cognitive theory perspective. Issue 2 (25th January 2022) - Cai, Yang; Shi, Wendian
ABSTRACT: The purpose of this paper is to investigate the underlying mechanism of the community climate on knowledge-sharing intention in virtual communities. Based on social cognitive theory, a theoretical model was developed and empirically tested using a web-based survey of 525 members from an online question and answer (Q&A) community in China. Results showed that knowledge-sharing self-efficacy and outcome expectation played a chain mediation role in the relationship between the community climate and knowledge-sharing intention. This study is among the first to examine whether and how community climate influences knowledge sharing. Our research findings unpack the mechanism of the community climate on knowledge-sharing intention, and provide practical insights on how to use community climate to facilitate users to share knowledge in online Q&A communities.